The Ottoman Government and the Sanusiyya: A Reappraisal - Gall, Michel Le (International Journal of Middle East Studies, 1989)
The historiography of the Sanusiyya, if one can apply such a term to the literary crop of roughly a century dealing with this North African tarīqa (pl. turuq, Sufi brotherhood), falls into three distinct categories. The earliest writings appeared in the 1880s, thirty years after the tariqa had taken root in Cyrenaica (then the Ottoman province of Benghazi). The works of French authors such as Charmes, Rinn, Duveyrier, Le Chatelier, and co-authors Depont and Coppolani were all marked by the concerns of the French colonial and protectorate authorities in Algeria and Tunisia. According to Duveyrier, a Saharan explorer of repute and the crudest exponent of this group's views, not only were the Sanusis a band of fanatics given to murdering innocent missionaries and explorers, but they were also in the vanguard of the turuq inspired by the Pan-Islamic rhetoric of the Ottoman sultan and aligned against French colonialism in Muslim North Africa. Only this combination of factors could account for the pervasive and determined resistance to French policies in the region. Along with the Sanusiyya, Duveyrier singled out for attack a North African sheikh and confidant of the Ottoman sultan, Muhammad Zafir al-Madani. Charmes, Rinn, Le Chatelier, and Depont and Coppolani, while less vitriolic in their tone, certainly had the same general approach. The analysis of this “Algerian school” was dismissed at the turn of the century by two eminent Orientalists, Christiaan Snouck Hugronje and Carl Heinrich Becker. A generation later, European fears of the turuq diminished in the wake of World War I, as new ideologies and forces came to dominate a transformed Pan-Islamism. This notwithstanding, some of the suppositions of the early French authors were adopted by later scholars and have since been quoted and requoted.
Keywords: Tripoli – 1551-1911